A solution to the problem of proper segment positioning in the course of digit formation. (November 2018) - Pecze, László
Abstract: Digit formation requires a robust process. Both digit number and digit identity are precisely controlled. Alan Turing and Lewis Wolpert proposed two different mathematical processes for digit formation, yet neither of them is completely satisfactory. In this study, a process called "French-flag driven Turing patterning" is presented that takes the advantages of both previous systems. Four components have been considered: I) a short-range activator (diffusion factor), II.) a long-range inhibitor (diffusion factor) and III) a very-long acting diffusing inhibitor or "French-flag factor", as well as IV) a non-diffusing, cell-autonomous transcription factor. The latter is responsible for the production of the activator and the long-range inhibitor. The "French-flag factor" is produced at one end of the one dimensional domain but its production decreases with time allowing the formation of the Turing pattern. Thus, the system becomes fast and extremely robust; peaks are formed always at the same position and it can support even 20% differences in the size of domains. The experimental findings derived from the examination of digit patterning are in full agreement with the results of the theoretical model. Although less experimental works are available, the presented "French-flag driven Turing patterning" mechanism might be a universal mechanism how nature produces highly reliable developmental segments.